1994
DOI: 10.1038/nsb1194-771
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of the transducin-phosphodiesterase interaction

Abstract: In vertebrate rod cells, the activated alpha-subunit of rod transducin interacts with the gamma (regulatory) subunits of phosphodiesterase to disinhibit the catalytic subunits. A 22-amino acid long region of rod transducin involved in phosphodiesterase activation has recently been identified. We have used peptides from this region of rod transducin and from several other G protein alpha-subunits to study the nature and specificity of the G protein alpha-effector interaction. Although peptides derived from rod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Rarick et al (16) found that a 22-amino acid peptide (␣ t residues 293-314) activates PDE. Within this region, Spickofsky et al (17) identified five residues in which substitutions of homologs from other ␣ subunits block PDE activation by peptides. Three of these residues are in the ␣4 helix and two are in the ␣4/␤6 loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarick et al (16) found that a 22-amino acid peptide (␣ t residues 293-314) activates PDE. Within this region, Spickofsky et al (17) identified five residues in which substitutions of homologs from other ␣ subunits block PDE activation by peptides. Three of these residues are in the ␣4 helix and two are in the ␣4/␤6 loop.…”
Section: Discussionmentioning
confidence: 99%
“…We found two regions of sequence in which mutations impaired the ability of ␣ i2 to inhibit adenylyl cyclase, the amino terminus of ␣3 and the ␣4/␤6 loop. The ␣4/␤6 loop is also important for the effector interactions of ␣ s (12) and ␣ t (16,17). These substitutions did not cause as much of a decrease in adenylyl cyclase inhibition as the Switch II mutations did, suggesting that Switch II residues are the primary contributors to the interaction between ␣ i2 and adenylyl cyclase.…”
mentioning
confidence: 95%
“…Sites of chemical cross-linking of the P␥-subunit to G t ␣ were localized to within the ␣4-␤6 loop (14,15). A study using substituted peptides identified five nonconserved effector residues within this region (16). Despite the large body of evidence, the significance of the G t ␣ ␣4-␤6 region in the effector interaction remains unclear.…”
mentioning
confidence: 99%
“…Several mutants with Ala substitutions of residues from the ␣4/␤6 loop had impaired binding to R* and reduced degrees of activation (11). Interestingly, this R* binding site overlaps with a region of G t ␣, G t ␣-293-314, that has been implicated in the transducin-effector interaction (12)(13)(14)(15)(16). A synthetic peptide, G t ␣-293-314, corresponding to the ␣4-␤6 region was shown to activate PDE in vitro and to bind to P␥ (12,13).…”
mentioning
confidence: 99%
“…The latter contacts have been localized to the switch II region, ␣ 3 -␤ 5 loop and ␣ 4 -␤ 6 loop of the RasD (42-44, 48). Of these, the ␣ 4 -␤ 6 loop is thus far the only region postulated to be involved in the selectivity for PDE stimulation based upon peptide saturations (46). In this study, we identify a new regulatory interface between the HD t and P␣␤ for which we propose a novel mechanism for G␣-effector regulation.…”
Section: Discussionmentioning
confidence: 89%